METHODS OF TEACHING FOREIGN LANGUAGES USING DIGITAL TECHNOLOGIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article discusses the advantages of using innovative and communicative information technology, which are the main factor in improving the quality of education and foreign language instruction. This article explores current issues of the use of information technology in teaching a foreign language. The introduction of new information technology in the educational process and in teaching a foreign language is an urgent requirement of today. This technology supposes using not only the most modern technical equipment, new forms and methods of teaching, but also a completely new approach to the teaching process, which helps to implement the principle of interactive, communicative-based teaching and provides individualization and differentiation based on features of trainees, their level and inclination.